Psycho-social factors associated with premature ejaculation among the patients attending in a tertiary level psychiatric hospital, Dhaka, Bangladesh (Bangladesh Journal of Psychiatry, 2020)
Premature ejaculation (PE) has been considered as the most common male sexual dysfunction affecting men and their partners. The objective of the study was to find out the proportion of PE, associated psycho-social factors and psychiatric co- morbidities among the patients attended in the Sexual Dysfunction Clinic of National Institute of Mental Health, Dhaka, Bangladesh. This was a cross-sectional study conducted from August 2017 to June 2018. For this purpose 280 male patients with complaints of sexual dysfunction aged from 18 to 60 years were selected by convenient sampling technique. A semi-structured, self-administered questionnaire containing socio-demographic variables, Bangla version of the premature ejaculation diagnostic tool (PEDT), Bangla version of the depression anxiety stress scales (DASS 21-BV) were applied to assess their PE and associated depression, anxiety and stress respectively. The results showed that, mean (+SD) age of the respondents was 38.8 (+8.44) years and 26.4% of the respondents were found to have PE. Presence of PE was slightly higher (55.4%) among the older age group (aged 41-60 years) than the younger age group (aged 18-40 years). Chi-square test showed significant association with religion, smoking status and psychiatric co-morbidities with presence of PE (p